The Interplay of Attitudes and Effectiveness: A Study on Financial Education among Young People in the Republic of Serbia - Đokić, Danica; Kuleto, Valentin; Popović Šević, Nevenka; Ilic, Milena; Stojaković, Dušan; Talaghir, Laurentiu-Gabriel; Rusu , Georgiana (Journal of Economic Development, Environment and People, 2023)
This paper describes the current state of young people’s attitude towards the world of finance and their need for financial education. Today, financial education is already practiced in many European countries, but this is not the case in the Republic of Serbia. However, research shows that financial literacy is one of the necessary skills for young people in the 21st century. The research results were presented on a sample of 175 people (exploratory research) aged between 18 and 35 from Serbia. The attitude of the respondents towards finances was presented, their financial habits were examined, and the results were presented using the method of descriptive statistics. Financial literacy plays a crucial role in promoting sustainable development and green finance by empowering individuals to make informed decisions that contribute to economic stability and growth.